SOSIALISASI PERATURAN WALIKOTA NOMOR 21 TAHUN 2013 TENTANG PROSEDUR DAN TATA CARA PEMBERIAN IZIN USAHA PARIWISATA KOTA DUMAI (STUDI KASUS WISATA KARAOKE) - Deby Meilani; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Karaoke business development in Dumai city has caused unrest in society as development of a beauty salon disguised as a karaoke place, there are no ragulations governing the operational hours and tax revenues are not balance by amount of karaoke place in Dumai city. Therefore, the government of Dumai city create a new policy that is expected to overcome these problems. The Mayor’s Rule Number 21 at 2013 about The Procedure granting the city’s tourism business license in Dumai city is a new policy. This news policy needs to be socialization as a first step of implementation, particulary the karaoke Tourism. The purpose of this research was determine, describe and analyze the policy socialization in karaoke places that performed by Departement of culture, tourism, youth and sport and police force civil service by forming a technical team.The concept of the theory used is a communication theory that consist of the communicator, the contents of the message, the media used, the communicant, and the effects after socialization. This research uses qualitative research metods to study descriptive data. In collecting the literature study using snowball sampling.After the research, it was found that socialization by the technical team is still considered optimal. Many of the employers and the public karaoke users and non-users are not aware of any karaoke new policy in dumai city, so there are still many karaoke places tha do not obey with the policy that has prevailed.Key Word : Socialization, The Ragulation of Mayor, Karaoke